Experimental Study on AA6005-T6 Material Welded with Friction Stir Welding Using Impact Test: Studi Eksperimental Pada Material AA6005-T6 Dilas dengan Friction Stir Welding Menggunakan Uji Impak - Suprayoga, Achmad; Mulyadi, Mulyadi (Universitas Muhammadiyah Sidoarjo, 2021)
The welding technique is often the choice in the joining process because of its light weight and relatively simple characteristics. Friction Stir Welding (FSW) is a welding method that was created and developed by The Welding Institute (TWI) in 1991. This easy, fast, and environmentally friendly welding process has been widely applied to construction, especially aluminum materials. The material used in the experiment was AA 6005-T6 6mm thick with varying tool speed parameters 765 1208 1907 3020 (rpm), feed rate 24 43 65 90 (mm/m), engine tilt, pin model (hexagonal, taper square, taper cylinder, cylinder), as well as an incision depth of 0.05 0.1 0.15 0.2 (mm). Using the Taguchy and ANNOVA methods as calculations and data processing. The test carried out is the impact test of the Charpy method using the ASTM E23 standard. After calculating with the Minitab 19 application, it was found that the most influential factor on the impact strength was the engine speed parameter of 765rpm which contributed 28.95%. Keywords: Welding Technique, Friction Stir Welding, Taghuchy, ANNOVA, impact test